Biomimetic cardiac tissue chip and murine arteriovenous fistula models for recapitulating clinically relevant cardiac remodeling under volume overload conditions - Waldrop, Tatyana Isayeva; Graham, Caleb; Gard, William; Ingle, Kevin; Ptacek, Travis; Nguyen, Nguyen; Lose, Bailey; Sethu, Palaniappan; Lee, Timmy (Frontiers in Bioengineering and Biotechnology, 2023)
Cardiovascular events are the primary cause of death among dialysis patients. While arteriovenous fistulas (AVFs) are the access of choice for hemodialysis patients, AVF creation can lead to a volume overload (VO) state in the heart. We developed a three-dimensional (3D) cardiac tissue chip (CTC) with tunable pressure and stretch to model the acute hemodynamic changes associated with AVF creation to complement our murine AVF model of VO. In this study, we aimed to replicate the hemodynamics of murine AVF models in vitro and hypothesized that if 3D cardiac tissue constructs were subjected to “volume overload” conditions, they would display fibrosis and key gene expression changes seen in AVF mice. Mice underwent either an AVF or sham procedure and were sacrificed at 28 days. Cardiac tissue constructs composed of h9c2 rat cardiac myoblasts and normal adult human dermal fibroblasts in hydrogel were seeded into devices and exposed to 100 mg/10 mmHg pressure (0.4 s/0.6 s) at 1 Hz for 96 h. Controls were exposed to “normal” stretch and experimental group exposed to “volume overload”. RT-PCR and histology were performed on the tissue constructs and mice left ventricles (LVs), and transcriptomics of mice LVs were also performed. Our tissue constructs and mice LV both demonstrated cardiac fibrosis as compared to control tissue constructs and sham-operated mice, respectively. Gene expression studies in our tissue constructs and mice LV demonstrated increased expression of genes associated with extracellular matrix production, oxidative stress, inflammation, and fibrosis in the VO conditions vs. control conditions. Our transcriptomics studies demonstrated activated upstream regulators related to fibrosis, inflammation, and oxidative stress such as collagen type 1 complex, TGFB1, CCR2, and VEGFA and inactivated regulators related to mitochondrial biogenesis in LV from mice AVF. In summary, our CTC model yields similar fibrosis-related histology and gene expression profiles as our murine AVF model. Thus, the CTC could potentially play a critical role in understanding cardiac pathobiology of VO states similar to what is present after AVF creation and may prove useful in evaluating therapies.